Intelligent digital control of dynamic braking of industrial robots - L MA Shraim; A A Vnukov (RUDN Journal of Engineering Research, 2013)
The article discusses issues related to the implementation of the digital motor control. Developed for this purpose a block diagram of the intelligent control algorithms and software that allows you to perform simulation in MatLab and Simulink, get depends, to draw conclusions and to recommend to the principle of fuzzy control and the ability to support the operation of variable frequency drive with AD without overheating the windings, ie in close to the nominal operation.